Change in hazard rates of recurrence over time following diagnosis of endometrial cancer: An age stratified multicentre study from the FRANCOGYN group. Issue 12 (December 2018) - Ouldamer, Lobna; Bendifallah, Sofiane; Body, Gilles; Canlorbe, Goeffroy; Touboul, Cyril; Graesslin, Olivier; Raimond, Emilie; Collinet, Pierre; Coutant, Charles; Lavoué, Vincent; Lévêque, Jean; Bricou, Alexandre; et al.
Abstract: Purpose: Predicting the pattern of recurrence can aid in the development of targeted surveillance and treatment strategies. The objectives of this study were to identify patterns of recurrence in women with operable endometrial cancer (EC) and to identify high-risk periods for recurrence in function of age. Patients and methods: The data of 1153 women who received primary surgical treatment for stage I-III EC between January 2001 and December 2013 were abstracted from a prospectively maintained multicentre database. The time to first recurrence was calculated from the date of diagnosis, and the associated hazard function was examined to determine the peak risk period of recurrence. We categorized age at diagnosis as <65 and ≥ 65 years old and analysed the hazard rate (HR) by stratifying age groups. Results: Women with EC aged ≥65 years maintain a significant recurrence rate during follow-up whatever the stratification (locoregional recurrence, distant recurrence, ESMO/ESGO/ESTRO subgroup). Multivariable Cox proportional hazard regression showed that the increased risk of recurrence of EC was associated with advanced age, advanced disease ESMO/ESGO/ESTRO subgroup but not with initial treatment received. Conclusion: The annual HR of recurrence is not uniformly distributed over time but is dynamic and markedly determined by prognostic factors at diagnosis.